2018
DOI: 10.21512/lc.v12i3.4063
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Reading (ER) Practices and the Development of Language Fluency

Abstract: This research aimed at investigating the Extensive Reading (ER) practices of the students and the development of language fluency. The design of the research was a qualitative study using purposive sampling technique. The data were collected by conducting interview and distributing questionnaire to 20 postgraduate students in Sebelas Maret University, Surakarta, Indonesia. Furthermore, the research revealed some findings on the types of reading materials preferred, reasons and benefits of reading, the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The frequency distribution and percentage after the teaching and learning process of test 1 and test 2 can be seen in Table 5. (Januarty, 2018). Furthermore, the researcher interviews the participants personally.…”
Section: Resultsmentioning
confidence: 99%
“…The frequency distribution and percentage after the teaching and learning process of test 1 and test 2 can be seen in Table 5. (Januarty, 2018). Furthermore, the researcher interviews the participants personally.…”
Section: Resultsmentioning
confidence: 99%
“…Sadoski (2015), as cited in Aprilia, states The aim of teaching reading is to encourage students or learners to discover knowledge from the word combination in the text and to do so in a consecutive manner at a fair pace without actually expressing what is being read. Teaching reading is controlled by teachers and students and systems or content (Haris et al, 2019;Januarty, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies by Mikami (2016) and Januarty (2018) revealed that students who have experienced extensive reading strongly believed in its importance and benefits toward improving their language proficiency. However, the student's motivation for the continuous process of reading could have been more stable.…”
Section: Related Research Reportsmentioning
confidence: 99%